2015
DOI: 10.1002/jbmr.2548
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 Regulation of CXCL12 Cellular, Temporal, and Spatial Expression Is Essential During Fracture Repair

Abstract: The cellular and humoral responses that orchestrate fracture healing are still elusive. Here we report that bone morphogenic protein 2 (BMP2)-dependent fracture healing occurs through a tight control of chemokine C-X-C motif-ligand-12 (CXCL12) cellular, spatial, and temporal expression. We found that the fracture repair process elicited an early site-specific response of CXCL12+-BMP2+ endosteal cells and osteocytes that was not present in unfractured bones and gradually decreased as healing progressed. Absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Local expression of CXCL12 has been shown to attract hematopoietic and endothelial progenitors to ischemic sites ( 87 , 88 ). It is also expressed in bone marrow stroma cells ( 89 ) and has been reported to be upregulated at the endosteal surface around the injured bone from 7 to 14 days postsurgery ( 89 ). However, in other studies, CXCL12 levels have been reported to peak at different time points postfracture.…”
Section: Changes In the Expression Of Chemokines In Response To Fractmentioning
confidence: 99%
“…Local expression of CXCL12 has been shown to attract hematopoietic and endothelial progenitors to ischemic sites ( 87 , 88 ). It is also expressed in bone marrow stroma cells ( 89 ) and has been reported to be upregulated at the endosteal surface around the injured bone from 7 to 14 days postsurgery ( 89 ). However, in other studies, CXCL12 levels have been reported to peak at different time points postfracture.…”
Section: Changes In the Expression Of Chemokines In Response To Fractmentioning
confidence: 99%
“…These findings not only strengthen the importance of mechanical loading (i.e., exercise) in preventing bone metastases, but also highlight a key role of osteocytes in the establishment of metastatic breast cancer. Another aspect that supports a regulatory role of osteocytes during early stages of breast cancer bone metastasis is that osteocytes produce CXCL12 [64], a chemokine involved in tumor cell homing and dormancy [65,66]. Through activation of the CXCL12-CXCR4 signaling cascade in cancer cells, osteocytes could consequently mediate cancer cell homing to bone.…”
Section: The Role Of Osteocytes In Breast Cancer Bone Metastasismentioning
confidence: 99%
“…In addition, it has been shown that C‐X‐C motif chemokine ligand 12 (CXCL12) signaling through the C‐X‐C chemokine receptor type 4 (CXCR4) receptor in cancer cells plays an important role in the retention and homing to bone of both cancers that develop in the bone marrow, as well as metastatic cancer cells . Osteocytes produce CXCL12 and therefore could activate the CXCL12‐CXCR4 signaling axis in cancer cells, favoring their homing to bone . However, alternatively it is also possible that osteocytes prevent the migration and arrival to bone of metastatic breast cancer cells.…”
Section: Role Of Osteocytes In Tumor Metastasis To Bonementioning
confidence: 99%